Theory, practice and research in initial teacher education in Brazil: challenges and alternatives - Marcondes, Maria Inês; Leite, Vânia Finholdt Angelo; Ramos, Rosane Karl (European Journal of Teacher Education, 2017)
The main goal of this paper is to discuss initial teacher education in the Brazilian context, by presenting three educational experiences that prioritise the connection between theory, practice and research in initial teacher education. The paper is the result of a literature review and a document analysis. The theoretical framework for this paper includes the concepts of reflective practice and research, critical thinking, collective collaborative educational processes for the professional development of student teachers, and joint research as well as activities between university and schools. We briefly present and discuss National Curricular Guidelines, two initial teacher education experiences, and the Government Grant Programme for Initial Teacher Education, the so-called PIBID. The paper concludes that the integration of theory, practice and research is of paramount importance for the improvement of initial teacher education. A discussion of the remaining challenges and possibilities for initial teacher education in Brazil are also discussed.